2000
DOI: 10.1034/j.1600-0773.2000.d01-25.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Aluminium Compounds Given Orally to Mice on Al Tissue Distribution and Tissue Concentrations of Essential Elements

Abstract: To evaluate the risk of gastrointestinal long-term aluminium (Al) exposure, aluminium distribution and the levels of the following essential elements: Ca, Mg, Zn, Cu, and Fe in tissue were studied. Aluminium was administered in drinking water as aluminium chloride, dihydroxyaluminium sodium carbonate or aluminium hydroxide. Mice (strain Pzh:SFIS) were exposed to a total dose of 700 mg Al in long-term treatment (for each Al compound n = 15). Concentrations of Al, Ca, Mg, Zn, Cu, and Fe in stomach, kidneys, bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence, in a future study, internalization within sperm cells could be qualitatively studied by various microscopy techniques and quantitatively by ICP-AES to support this hypothesis. A study by Długaszek et al (2000) also showed varying concentrations of Al in tissues of mice gavaged with Al. Significant changes in mouse sperm parameters due to exposure to iron oxide NPs were also reported (Varzeghani et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Hence, in a future study, internalization within sperm cells could be qualitatively studied by various microscopy techniques and quantitatively by ICP-AES to support this hypothesis. A study by Długaszek et al (2000) also showed varying concentrations of Al in tissues of mice gavaged with Al. Significant changes in mouse sperm parameters due to exposure to iron oxide NPs were also reported (Varzeghani et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Panlab Domingo et al (1993) Essentially Al free Purified diet Fosmire et al (1993) Commercial rodent chow Fosmire et al (1993) 7 Dyets purified diet and Golub and Germann (2001) a Panlab Colomina et al (1998) Purina 5001C Oteiza et al (1993 Purified diet Oteiza et al (1993) 64.5 Commercial mouse chow Długaszek et al (2000) Purina 5001 rodent chow Guo et al (2001Guo et al ( , 2002Guo et al ( , 2005bGuo et al ( , 2006Guo et al ( , 2009 Gupta et al (1986) 8300 Purina Rodent Chow 5001 Fleming and Joshi (1987) Altromin 1320 Gawlik et al (1987) Sniff diet Gawlik et al (1987) 7.3 Altromin C Gawlik et al (1987) 66 Purina Certified 5002 rodent chow Hicks et al (1987) 60 Panlab Domingo et al (1987b) a Wayne Lab Blox Fulton et al (1989) and 135…”
Section: -280mentioning
confidence: 99%
“…The Panel noted that most of the biochemical and toxicological studies did not measure the "normal" aluminium content of the basal diet fed to the animals, and therefore the stated dose in such studies is likely to be an underestimate of the total aluminium exposure. Thus, rat diets have been reported to contain 110 (Kandiah and Kies, 1994), 100 (Gupta et al, 1986), 5 (Glynn et al, 1995), and 51 mg aluminium/kg (Yokel et al, unpublished results cited by IAI, 2007), mouse diet to contain 131 and 64.5 mg aluminum/kg (Dlugaszek et al, 2000and Fosmire et al, 1993as cited by IAI, 2007, guinea pig diet to contain 47 (Golub et al, 1996a) and 60 mg aluminium/kg (Owen et al, 1994), and rabbit diet to contain 297, 1215 and 335 mg Al/kg (Fulton & Jeffery, 1990, Yokel and McNamara, 1985, and Yokel et al, unpublished results, as cited by IAI, 2007. As an example, for a rat diet containing aluminium at a concentration of 100 mg/kg, applying the default conversion factors indicates base-line doses of aluminium equivalent to 15 mg/kg bw for mice and 10 mg/kg bw for rats.…”
Section: Biological and Toxicological Datamentioning
confidence: 99%
“…The distribution of aluminium in animals after oral exposure has been determined in a number of studies (Cranmer et al, 1986;Deng et al, 2000;Dlugaszek et al, 2000;Domingo et al,. 1993;Greger and Donnaubauer 1986;Julka et al, 1996;Ogasawara et al, 2002;Sutherland and Greger 1998;Walton et al, 1995;Yokel and McNamara 1985;Zafar et al, 1997as cited by IAI, 2007.…”
Section: Animal Studiesmentioning
confidence: 99%